China's Logistics Industry Transformation in The Context of The Covid-19 Pandemic - Xuemei An; Victoria А. Chernova (Communications of International Proceedings, 2022)
This article examines the impact of the COVID-19 pandemic on the international economy, as well as how border closures and restrictions on transport between countries have affected transport logistics chains. The main strategies for the development of global transport companies in the context of the pandemic are also identified by the example of a logistics company for the delivery of goods by different transport. It is also worth noting that in the context of the global economic crisis in the logistics industry, the acceleration of digital transformation processes is noted. The COVID-19 pandemic has transformed business practices, leading to dynamic changes in workflow automation. The digitalization of the logistics industry began to gain momentum rapidly. The transformation of the logistics business is developing in the following directions [2]: creation of digital technologies in interaction with the client during order processing and cargo transportation; growth of online sales in the B2B segment during a pandemic - a change in the format of sales, digitalization of customer service standards; ordering transportation from a mobile device; the emergence of a separate industry "Mobile carriers"; transition to remote work of employees; development of online trading. translation of all global logistics events into an online format. During the pandemic, many logistics companies decided to move their work “on a new track”. The IT revolution has begun in logistics. The role of IT platforms for logistics companies has increased in order to exchange tariffs and rates, and interact with contractors. Real-time supply chain management (SCV) has ceased to be something incomprehensible and today it is becoming a necessary condition. Real-time data is now in demand by an increasing number of customers, which means that logistics companies must focus on this issue. A highly automated supply chain in today's environment is becoming very popular. Now the client gets the opportunity to order transportation on the digital logistics platform by clicking on a button in the mobile application. It is these digitalization systems that will be in demand in the future. Robotic warehouse operations, unmanned stackers and transporters instead of loaders are already becoming a reality in many companies. As a result of automation and optimization of all logistics processes, the need for logisticians who previously performed operational functions is falling. Such a profession as a freight forwarder is a thing of the past. Due to the emergence of electronic Internet services, services now connect the cargo owner with agents, carriers, terminals, insurance companies and picking up delivery schemes. It remains only to agree on the issue of document flow and financing. At the same time, logistic architects with multi-competence in the areas of procurement, warehouse, transport, manufacturing, distribution logistics, production process management, mathematical analysis tools, and knowledge of IT technologies will have a high value. Such specialists are needed to build effective logistics systems in a company.
Keywords: strategy; international; logistics; pandemic; COVID-19; transport company; digitalization; digitalization; information technology.